Chemical characterization of black and red inks inscribed on ancient Egyptian papyri: The Tebtunis temple library. (August 2017) - Christiansen, Thomas; Buti, David; Dalby, Kim Nicole; Lindelof, Poul Erik; Ryholt, Kim; Vila, Anna
Abstract: This article presents the results of a study on the chemistry of the black and red inks used on papyri from the only institutional library to survive from ancient Egypt – the Tebtunis temple library. The aim of the study is to identify, through the chemistry of the inks, if certain papyrus fragments from the library are related. The papyri are examined using non-invasive analytical methods, including optical microscopy, X-ray fluorescence (XRF) spectroscopy, scanning electron microscopy-energy dispersive spectroscopy (SEM-EDXS), Raman spectroscopy and fiber optics reflectance spectroscopy (FORS). Via these techniques, inks undocumented in the analytical record are detected. Moreover, the analytical results are compared to other assemblages of ancient manuscripts from the Hellenistic and Roman periods (c. 200 BCE–400 CE) and provide new information on the history of the production of ink in the ancient Mediterranean cultures. Highlights: The first analysis of inks on papyri from an ancient Egyptian library is reported. Black and red inks previously undocumented in the analytical record are described. The earliest conscious use of metalloids in black ink is detected.